Improving Student Learning Outcomes through Community-based Research: The Poverty Workshop. (April 2019) - Mayer, Brian; Blume, Amelia; Black, Candace; Stevens, Sally
Engaged learning extends education outside of the formal classroom through internships, experiential learning, and community- or service-based learning. To better understand the potential of engaged learning in improving student learning outcomes and encouraging students to pursue STEM-based careers, we describe the development of a community-based research experience related to poverty and report on improvements in students' self-reported competencies in generalized self-efficacy, research skills, and science motivation. We compare these outcomes to those of students in a traditional sociology methods class to determine whether the engaged learning experience improves learning outcomes. Our findings indicate that students in the engaged learning course report higher generalized self-efficacy and research skills compared to students in the traditional methods course. Based on these findings, we propose a set of strategies for other colleges and universities to integrate engaged learning courses into their curriculum.